Principals in Preschool Management and Leadership: A Necessary Combination to Ensure That Preschool Teachers Are Given Conditions to Be Responsible for Teaching in Preschool - Anna Öqvist; Sara Cervantes (Education Sciences)
Following the educational reforms of 2010 and the revision of the curriculum in 2018, Swedish preschool principals have a special responsibility for ensuring that preschool teachers have the necessary conditions to assume their responsibility for the teaching and to lead the work team. This indicates that integrating leadership with management is essential for a sustainable and successful preschool education. This study explores this assumption. Building on the concepts of management and leadership, with a qualitative research design, this study analyses data from seven interviews with preschool principals. The results showed a lack of a combination of management and leadership among the principals in relation to their special responsibility of ensuring that preschool teachers are given conditions necessary to be responsible for teaching in the preschool. The principals either lacked both management and leadership or focused on management only with a lack of leadership. Our findings suggest the necessity for principals to combine management and leadership and move from a previous flat organisational structure towards a focus on increasing preschool teachers’ responsibilities and leadership within the work team. Support for principals is needed to be able to perform a combination of management and leadership when their mission is complex and time-consuming.